2014
DOI: 10.1093/mnras/stu636
|View full text |Cite
|
Sign up to set email alerts
|

Massive compact galaxies with high-velocity outflows: morphological analysis and constraints on AGN activity

Abstract: We investigate the process of rapid star formation quenching in a sample of 12 massive galaxies at intermediate redshift (z ∼ 0.6) that host high-velocity ionized gas outflows (v > 1000 km s −1 ). We conclude that these fast outflows are most likely driven by feedback from star formation rather than active galactic nuclei (AGN). We use multiwavelength survey and targeted observations of the galaxies to assess their star formation, AGN activity, and morphology. Common attributes include diffuse tidal features i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
137
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(154 citation statements)
references
References 205 publications
(214 reference statements)
17
137
0
Order By: Relevance
“…ALMA is a partnership of ESO (representing its member states), NSF (USA) and NINS (Japan), together with NRC (Canada), NSC and ASIAA . Top: median stacked spectra of "K+A" (French et al 2015;blue), "active" (Sell et al 2014;orange), and "A" type (black) post-starburst galaxies. Bottom: Hδ A vs. D n 4000 for the same three post-starburst samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALMA is a partnership of ESO (representing its member states), NSF (USA) and NINS (Japan), together with NRC (Canada), NSC and ASIAA . Top: median stacked spectra of "K+A" (French et al 2015;blue), "active" (Sell et al 2014;orange), and "A" type (black) post-starburst galaxies. Bottom: Hδ A vs. D n 4000 for the same three post-starburst samples.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 4, we show for comparison the low-redshift "K+A" post-starburst galaxies in French et al (2015), an "active" poststarburst galaxy in the Sell et al (2014) sample observed in CO by Geach et al (2013), and star-forming and quiescent galaxies at z∼0 (COLDGASS, Saintonge et al 2011; ATLAS-3D, Cappellari et al 2011Cappellari et al , 2013Young et al 2011;Davis et al 2013Davis et al , 2014and MASSIVE, Davis et al 2016) …”
Section: Molecular Gas Massesmentioning
confidence: 99%
“…(Similar Lyα signatures were identified among quenching galaxies by Taniguchi et al 2015. )They interpreted these observational signatures as related to the compact galaxies having enhanced feedback in the ISMdue to ahigher surface density of star formation than their more extended counterparts (see also Diamond-Stanic et al 2012;Sell et al 2014;Alexandroff et al 2015;Heckman & Borthakur 2016), plausibly leading to the truncation of future star formation.…”
Section: Energy Sources: Quenching Agents In Qgsmentioning
confidence: 99%
“…Indeed, extremely compact star-forming regions, with SFRs of ≈200 M yr −1 and sizes ≈100 pc, have been attributed to driving ≈1000 km s −1 outflows (Heckman et al 2011;DiamondStanic et al 2012;Sell et al 2014). However, maximum velocities as high as that observed around the HR-B radio structure (i.e., v max ≈ 1100 km s −1 ) are not seen in non-AGN host galaxies with SFRs comparable to that of the "Teacup" AGN (i.e., SFRs ≈ 10 M yr −1 ; e.g., Genzel et al 2011;Arribas et al 2014) and compact starbursts are often associated with flatter radio spectral indices than that observed here (Murphy et al 2013).…”
Section: Star Formationmentioning
confidence: 99%